EVALUASI KUALITAS LAYANAN PERPUSTAKAAN KAMPUS INAIS DARI PERSPEKTIF PENGGUNA: PENDEKATAN KUALITAS DIMENSI SERVQUAL - Muhamad Alwi Muwaffiq; Ima Rahmawati; Muhamad Robie Awaludin (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2026)
This study attempts to understand how library users perceive the quality of library services. Using qualitative methods based on the dimensions of SERVQUAL (Tangibles, Reliability, Responsiveness, Assurance, and Empathy). Involving detailed interviews with ten regular users who have different levels of education and frequently visit the library. The information collected was analyzed to find out what users think, what they expect, and how happy they are with the library services. The results showed that users were most positive about the aspects of Assurance and Responsiveness, which indicate that the staff are professional and responsive. However, the aspects of Tangibles and Empathy still need to be improved, such as providing more physical resources and paying attention to what each user needs. This study concludes that to make library services better, libraries can improve their facilities, train staff regularly, and offer more flexible service hours. This study is important to improve library services based on what users want and can help create policies for quality information services in schools. Keywords: Library services, User satisfaction, Qualitative, SERVQUAL, Quality evaluation